Implementation Of Strengthening Pancasila Student Profiles In Islamic Religious Education Learning - Hamzah Irfanda; Nofitayanti (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2025)
The profile of Pancasila students is a character education that has begun to erode over time and is increasingly forgotten. In this character education, Pancasila Students are realized as the Profile of the Indonesian nation in the national and international arenas. The profile of Pancasila students is another name for the direction we take towards our educational goals. This type of research is descriptive qualitative research. Data collection instruments use interviews, observations and documentation studies. This study aims to determine the implementation of the Pancasila Student Profile Strengthening Project through Islamic Religious Education Subjects. The results of this study can be seen that ) Teachers prepare modules for school administration and as a guide in the learning process in schools, the importance of teaching modules in the learning process by teachers in the classroom so that the learning process can run well and structured can refer to the modules that have been provided and implemented so that the objectives, learning achievements can run well Based on this study, it can be concluded that teachers prepare modules for school administration and as a guide in the learning process in schools, the importance of teaching modules in the learning process by teachers in the classroom so that the learning process can run well and structured can refer to the modules that have been provided and implemented so that the objectives, learning achievements can run well. The teacher asks about the students' news and checks the students' attendance. The teacher provides an apperception of the importance of understanding the application of the meaning of competition in goodness and work ethic.